TINGKAT PATINASI DAN PEMBUNDARAN ARTEFAK LITIK SEBAGAI PETUNJUK POSISI STRATIGRAFIS DAN LOKASI ASAL PENGENDAPAN, KAJIAN ARTEFAK LEMBAH SUNGAI BAKSOKA - Muhammad Hidayat (Berkala Arkeologi, 2001)
The application of artefact analysis which includes patination and rounding rates which has been applied to a collection of artifacts from the Baksoka River basin has proven to be of great help in research. The results of this analysis are very helpful in obtaining a picture of the origin / initial location of a collection of artifacts mixed in their deposition. From the results of this analysis, it can be seen which river terraces contain artifacts, and finally an estimate of the chronology of these artifacts can be obtained.